Children and Armed Conflict. - Poulatova, Chaditsa (Cambridge Scholars Publishing, 2013)
At a time of escalating global conflict and instability, this book examines international efforts to protect children from the effects of war and armed conflict through the Convention on the Rights of the Child (CRC), especially article 38, and the Convention's Optional Protocol on the involvement of Children in Armed Conflict (OPAC). The principal focus of the book is on the existing UN established machinery for implementing the CRC and OPAC - the Committee on the Rights of the Child and its ..